Application of Multi-Year Training Works in Training Athletics in Training Cycles - Z.B.Khamraeva (Global Scientific Publishing, 2022)
This article provides information on the effectiveness of long-term training in athletics based on the application of training loads in training cycles.
Keywords: middle distance; running; healthy; young generation